Research on Electrical Automation Monitoring System Model of Power Plant Based on CAN Bus - Shu-chun Chen (Journal of Electrical and Computer Engineering)
Using the traditional manual operation mode to control the electrical equipment of the power plant was not only inefficient and unsafe but also difficult to adapt to the use of new equipment. Therefore, this article puts forward the research on the model of power plant electrical automation monitoring system based on CAN bus, which was of great significance to improve the operation monitoring ability and management efficiency of power plant electrical equipment. Based on the analysis of the design mode and main functions of electrical equipment automation control system in power plant, this article expounded on the characteristics of CAN bus communication mode and its advantages in realizing electrical equipment automation control. According to the hierarchical management and structural characteristics of the electrical automation monitoring system, the real-time database architecture of the monitoring system was established, the real-time data monitoring and processing method of the electrical monitoring system was given, and then the electrical automation monitoring system model of the power plant was proposed. The experimental results showed that the electrical automation monitoring system proposed in this article was effective and feasible for real-time monitoring of the operation of electrical equipment. The model construction method of the electrical automation monitoring system proposed in this article can provide theoretical reference and technical support for improving the control mode of electrical equipment in power plants.